Working-Class Gay and Bisexual Men - Appleby, George A. (Harrington Park Press, 2001)
Keywords: Services for; Services for; Bisexual men; Social work with gays; Gays; dept.swk; faculty_collection

Diversity, Oppression, and Social Functioning: Person-in-Environment Assessment and Intervention - Appleby, George A.; Colon, Edgar; Hamilton, Julia (Allyn and Bacon, 2001)
Keywords: Social work with minorities; Person-in-environment system; dept.swk; faculty_collection

Introduction - Flynn, D.S.; Siegel, E. (Gerontology and Geriatrics Education, 2001)
0 citations (Crossref) [2023-10-31]
Keywords: dept.swk

Distance learning in gerontological education: results and implications of a national survey - Tompkins, Catherine J.; Siegel, Elbert (Gerontology & Geriatrics Education, 2001)
This article reports data collected from a national survey of the Association for Gerontology in Higher Education’s (AGHE) member institutions conducted in 1998. The purpose was to explore current usage of distance learning in gerontological education. The findings suggest that distance learning is being implemented within various programs throughout the country with many others showing an interest. The strengths and limitations of using distance learning in gerontological education are discussed. [Article copies available for a fee from The Haworth Document Delivery Service: 1-800-342-9678. E-mail address: <getinfo@haworthpressinc.com> Website: <http://www.HaworthPress.com>]. © 2001 by The Haworth Press, Inc. All rights reserved.
6 citations (Crossref) [2023-10-31] Citation Key Alias: pop00279 tex.type: [object Object]
Keywords: dept.swk

Practice and theoretical knowledge-based theory for clinical and policy practice - Appleby, George Alan (Journal of Gay and Lesbian Social Services, 2001)
SUMMARY: Practice with working-class gay and bisexual men draws upon an ecological framework with a strengths perspective, which emphasizes the roles of culture, values, social class, social identity development, social categorization, social comparison, oppression and power, diversity, and stigma. This practice is based upon a process of developing an assessment and selecting a range of human service interventions. Ethnographic studies were conducted throughout the United States and Canada using a broad-based sample of working-class men to enhance our understanding of their needs and effective ways of helping. © 2001, Taylor & Francis Group, LLC.
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/170-732-264-616-422 tex.type: [object Object]
Keywords: And intervention; Assessment; Culture; Diversity; Ecology; Individual and group identity; Oppression and power; Social class; Stigma; Strengths; Values; dept.swk

"It was just realizing... that life isn't one big horror": A qualitative study of supported socialization - Davidson, L.; Haglund, K.E.; Stayner, D.A.; Rakfeldt, J.; Chinman, M.J.; Tebes, J.K. (Psychiatric Rehabilitation Journal, 2001)
This report describes the qualitative component of a large-scale study of supported socialization. Paralleling the recent advances made through supported housing, supported employment, and supported education, this approach seeks to increase the involvement of individuals with psychiatric disabilities in naturally occurring social and recreational activities in community settings of their choice. After a review of social relationships and psychiatric disability, we describe the Partnership Project and present findings from a series of qualitative interviews conducted with a subsample of participants. We then discuss the implications of these findings for the community integration of individuals with psychiatric disabilities.
90 citations (Crossref) [2023-10-31]
Keywords: adult; article; clinical article; dept.swk; education; employment; female; health program; housing; human; human relation; integration; life; male; mental disease; questionnaire; recreation; socialization; support group; therapeutic community